The impact of the tax administration act and aspects of the Constitution of South Africa on SARS' ability to collect taxes - Pillay, Prenusha (My University, 2016)
As the framework for the collection of revenue by SARS evolves to ensure taxpayer compliance, the protection of taxpayers’ fundamental rights should not be overlooked. This research will evaluate certain provisions of the recently enacted Tax Administration Act (the Act) against the background of the taxpayers’ rights to privacy, property and just administrative action. These rights are contained in the Constitution of South Africa, the supreme law of the land. The analysis suggests that the conduct of SARS in exercising its statutory powers as well as some of the provisions of the Act may conflict with taxpayers’ constitutional rights and that the remedies available in such situations are limited or do not offer taxpayers an effective mechanism to obtain remedial action. Key words: Bill of Rights, Constitution, Constitution of South Africa, constitutional right, just administrative action, legislation, Ombud, PAJA, Promotion of Administrative Justice Act, privacy, property, remedies, SARS, tax, tax administration, Tax Administration Act, Tax Ombud, taxation, taxpayer, taxpayer compliance.
A research report submitted to the Faculty of Commerce, Law and Management in partial fulfilment of the requirements for the degree of Master of Commerce Date: 31 March 2015
Keywords: Bill of Rights; Constitution of South Africa; SARS; Tax Administration Act; Ombud; Promotion of Administrative Justice Act; Legislation